(untitled) (Alberta, Canada, 1996)
This book is filled with practical ideas and straight talk aimed at aspiring and inexperienced teachers. This is a book of "how to" activities and concrete down-to-earth hints, methods, and useful ideas that address questions that have plagued all newcomers to the teaching profession.
Keywords: Teaching